Optimizing The Search Of Access Control Lists For IP Packet Filtering Applications - Seyed Mohamed Buhari Mohamed Ismail, (2003)
A highly secured network with improved network performance in transmission control protocol internet protocol (TCP IP) is the main aim of this research. Diffrent parts of this theses are devoted to the study and analysis of security and performance of the IP packet filtering. We have studied networks of varying sizes in order to make research results applicable to computer networks in general. The network for checking IP packet filtering rules was designed and analyzed for security aspects using expert system and neural networks. Further the performances of such secure rules were improved using parallel system and active networks.